INTERNALISASI NILAI KARAKTER ISLAMI MELALUI PROGRAM TAHFIDZ DAY PADA ANAK USIA DINI TK AL-WARDAH TERPADU II - Kholifatun Nisa; Salsabilla Nur Farodisa; Gita Candra Wulan; Winnuly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine in depth the implementation and impact of the Tahfidz Day program in the process of internalizing Islamic character values in early childhood at Al-Wardah Kindergarten. Character education in the early childhood phase has a strategic position in forming the foundation of personality, considering that this period is a developmental stage that is very sensitive to environmental stimuli. The Tahfidz Day program is implemented routinely every morning before core learning through a series of activities of congregational dhuha prayer, prayer reading, Quran recitation, and memorization of the Quran. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews with the principal and teachers, and documentation of activities during one month of program implementation. Data analysis is carried out through the stages of reduction, presentation, and systematic drawing of conclusions. The results of the study indicate that the Tahfidz Day program contributes to strengthening religious character, discipline, responsibility, patience, and mutual respect in children. Internalization of values occurs through a consistent habituation mechanism, educators' role models, and the creation of a religious and structured school culture. Repeated spiritual activities form a tendency for more stable and integrated behavior in children's daily lives. These findings confirm that integrating tahfidz (Quran recitation) activities into the routines of early childhood education institutions can be an effective strategy for building a sustainable moral and spiritual foundation. This program focuses not only on memorization but also on holistic character development as a long-term investment in developing a generation with noble morals.